Perancangan kawasan berorientasi transit dengan pendekatan water sensitive urban design - Dian Fitria; Haryo Winarso; Petrus Natalivan Indradjati (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
The Tegalluar and Gedebage areas in Rancanumpang Village have been identified as potential transit-oriented development (TOD) sites. However, these areas face challenges due to their low elevation, which leads to ground level reductions and seasonal flooding. To address these issues, it is crucial to incorporate a water-sensitive urban design (WSUD) approach into the development of an interconnected and integrated transit-oriented area. Therefore, this study aims to propose an alternative design for the Tegalluar transit-oriented area, focusing on factors such as density, diversity, design, destination accessibility, distance to transit, and environmental considerations. A fragmental method was applied at different stages of the design and this led to the development of an alternative conceptual design simulation for the transit-oriented area based on the desired factors.